Role of primary care in the COVID-19 response - World Health Organization. Regional Office for the Western Pacific (Manila : WHO Regional Office for the Western Pacific, 2020)
Primary care can play a significant role in the COVID-19 response by differentiating patients with respiratory symptoms from those with COVID-19, making an early diagnosis, helping vulnerable people cope with their anxiety about the virus, and reducing the demand for hospital services. This document provides national and subnational health managers, as well as staff at primary care facilities, with interim guidance on timely, effective and safe supportive management of patients with suspected and confirmed COVID-19 at the primary care level; and delivery of essential health services at the primary care level during the COVID-19 outbreak.
Keywords: Coronavirus Infections; Infection Control; Disease Outbreaks; Disease Outbreaks; Betacoronavirus; Primary Health Care